The simultaneous treatment of PC-3 cells with the DNA-demethylating agent decitabine and S-adenosylmethionine leads to synergistic anticancer effects - Schmidt, Thomas; Sticht, Carsten (Genes, 2024)
Background: Epigenetic dysregulation is a common feature of cancer. Promoter demethylation of tumor-promoting genes and global DNA hypomethylation may trigger tumor progression. Epigenetic changes are unstable; thus, research has focused on detecting remedies that target epigenetic regulators. Previous studies have suggested that concordantly targeting hypomethylation and hypermethylation is beneficial for suppressing both the oncogenic and pro-metastatic functions of cancer cells. Therefore, we aimed to investigate the effect of a combination of S-adenosylmethionine (SAM) and the demethylating agent decitabine on prostate cancer cells. Materials and Methods: Prostate cancer cells (PC-3) were treated with SAM, decitabine, or a combination of both. Proliferation, migration, invasion, and methylation assays were also performed. A transcriptome study was conducted to detect different gene clusters between the treatment groups, followed by analyses using the Kyoto Encyclopedia of Genes and Genomes pathway and ingenuity pathway analysis. Finally, to gain information on differential gene expression, promoter methylation studies were performed. Results: Groups treated with decitabine, SAM, or their combination showed reduced proliferative capacity. The decitabine-treated group showed a marginal increase in cell migration and invasion, whereas the SAM-treated and combination treatment groups showed reduced invasion and migration potential. Methylation assays demonstrated the restoration of decitabine-induced demethylation in prostate cancer samples, whereas the transcriptome study revealed the upregulation of different gene clusters between the treatment groups. Methylation studies confirmed that SAM could restore the decitabine-induced demethylation of proto-oncogenes, but it did not induce the re-methylation of tumor-suppressor genes. Conclusions: Combination treatment with SAM and decitabine had an additive effect and did not nullify each other.
Gesehen am 22.04.2025